2014
DOI: 10.12816/0008126
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Helicobacter Pylori Infection and the Severity of Rheumatoid Arthritis

Abstract: Background: The cause of autoimmune disease is not well-known; it is suggested that environmental, viral and bacterial factors might trigger the immune system. It was found that about 50% of the western and over 80% individuals in the developing countries are infected with Helicobacter pylori, a gram negative flagellated bacterium Because of its ability to induce chronic immune response in the host, it has been suggested that H. pylori has a role in the development and aggravation of autoimmune diseases. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Their results indicated that there was no significant difference in terms of incidence of new RA cases between H. pylori positive and negative patients during the course of the follow-up period [12]. Saad et al demonstrated no significant clinical or laboratory differences between Helicobacter pylori positive and negative patients in terms of rheumatoid [16]. Similarly, no difference was reported between RA and OA patients with Helicobacter pylori positive and negative findings regarding the clinical and laboratory results, which is consistent with the results of the present study.…”
Section: Discussion__________________________________mentioning
confidence: 95%
“…Their results indicated that there was no significant difference in terms of incidence of new RA cases between H. pylori positive and negative patients during the course of the follow-up period [12]. Saad et al demonstrated no significant clinical or laboratory differences between Helicobacter pylori positive and negative patients in terms of rheumatoid [16]. Similarly, no difference was reported between RA and OA patients with Helicobacter pylori positive and negative findings regarding the clinical and laboratory results, which is consistent with the results of the present study.…”
Section: Discussion__________________________________mentioning
confidence: 95%